Practices Of Infection Prevention And Associated Factors Among Healthcare Professionals At Community Health Clinics In Saudi Arabia, 2024 (The Review of Diabetic Studies, 2024)
Background: Globally, one of the most significant and complicated health issues is healthcare-associated infections (HCAI). HCAIs have been strongly linked to inadequate infection prevention strategies and pose significant obstacles to the safe and high-quality delivery of healthcare.The study aimed: To assess infection prevention practices and associated factors among healthcare professionals (HCPs) of community health clinics in Saudi Arabia.Methods: A cross-sectional study was conducted among a convenience sample of 128 HCPs of community health clinics in Saudi Arabia. Data were collected between January and February, 2024 through semi-structured questionnaire.Results: Of the study participants, only 39.1% had good infection prevention procedures and 37.5% knew enough about infection prevention methods. Higher educated health care professionals were substantially more likely to follow excellent infection prevention practices, which were linked to proper infection prevention knowledge and the availability of soap and hand washing facilities in community clinics.Conclusion: To improve the currently dropping infection prevention knowledge and practices among community HCPs, an efficient infection prevention training program must be implemented, along with a sufficient supply of basic infection prevention resources, ongoing monitoring, and supervision.